From trauma to harming others therapeutic work with delinquent, violent and sexually harmful children and young people - Nathanson, Ariel; Music, Graham, 1957-; Sternberg, Janine (London : Routledge, 2021)
From Trauma to Harming Others shows the approach of professionals from the world-renowned Portman Clinic, which specializes in work with violence, delinquency and sexual acting out. This book focuses on the intricacies of working with young people who display such worrying behaviours. Written by experienced and eminent authors, the chapters unpack central theories and open up original ideas describing a range of work with sexual offenders, compulsive pornography users and violent young people. The central theme of the book is trauma and how acting out can be understood as a way of managing the psychic pain of such trauma. The chapters are ingrained with understandings from the classical psychoanalytic traditions of the Portman and Tavistock Clinics, together with more recent thinking about trauma, rooted in neurobiological, developmentally and trauma informed theories. They emphasize the need for awareness of both the victim of trauma and the perpetrator within the same person presenting for help, while panning treatment. With insights and examples from experienced clinicians, this book will be of value to all those working with traumatized, acting out young people.
Introduction; 1: Key concepts developed at the Portman Clinic, Janine Sternberg; 2: Motiveless malignity: Problems in the psychotherapy of patients with psychopathic features, Anne Alvarez; 3: Considering Perversion from a Portman Clinic Perspective, Donald Campbell; 4: Young people in difficulty with Internet sex and pornography, Graham Music and Heather Wood; 5: Seeing and being seen: the psychodynamics of pornography through the lens of Winnicott`s thought, John Woods; 6: Working with mental hackers and backroom thinkers, Ariel Nathanson; 7: Angels and devils: sadism and violence in children, Graham Music; 8: Oedipal aspirations and phallic fears: on fetishistic presentation in childhood and young adulthood, Ann Horne; 9: Self-harm and the harm of others in adolescents, Tim Baker ; 10: "Securing the disaster zone. Assessing the damage. Sifting through the rubble": The early stages of psychotherapy with a traumatised boy, Patricia Allan; 11: Embracing darkness: clinical work with adolescents and young adults addicted to sexual enactments; 12: The history of the Portman Clinic, Marianne Parsons
Keywords: Juvenile delinquents; Child psychotherapy; Adolescent psychotherapy; Psychic trauma in children -- Treatment; Psychic trauma in adolescence -- Treatment; Conduct disorders in children -- Treatment; PSYCHOLOGY / Psychotherapy / Child & Adolescent; PSYCHOLOGY / Mental Health